A Novel Theranostic Nanoprobe for In Vivo Singlet Oxygen Detection and Real‐Time Dose–Effect Relationship Monitoring in Photodynamic Therapy. Issue 39 (7th August 2019) - Wang, Han; Wang, Zhaohui; Li, Yongkuan; Xu, Tian; Zhang, Qi; Yang, Man; Wang, Peng; Gu, Yueqing
Abstract: Singlet oxygen, as the main member of reactive oxygen species, plays a significant role in cancer photodynamic therapy. However, the in vivo real‐time detection of singlet oxygen remains challenging. In this work, a Förster resonance energy transfer (FRET)‐based upconversion nanoplatform for monitoring the singlet oxygen in living systems is developed, with the ability to evaluate the in vivo dose–effect relationship between singlet oxygen and photodynamic therapy (PDT) efficacy. In details, this nanoplatform is composed of core–shell upconversion nanoparticles (UCNPs), photosensitizer MC540, NIR dye IR‐820, and poly(acryl amine) PAA‐octylamine, where the UCNPs serve as an energy donor while IR‐820 serves as an energy acceptor. The nanoparticles are found to sensitively reflect the singlet oxygen levels generated in the tumor tissues during PDT, by luminescence intensity changes of UNCPs at 800 nm emission. Furthermore, it could also enable tumor treatment with satisfactory biocompatibility. To the best knowledge, this is the first report of a theranostic nanoplatform with the ability to formulate the in vivo dose–effect relationship between singlet oxygen and PDT efficacy and to achieve tumor treatment at the same time. This work might also provide an executable strategy to evaluate photodynamic therapeutic efficacy based on singlet oxygen pathway. Abstract : A Förster resonance energy transfer (FRET)‐based upconversion nanoplatform for monitoring 1 O2 in living systems is developed with the ability to evaluate the in vivo dose–effect relationship between 1 O2 and photodynamic therapy (PDT) efficacy. The nanosystem can sensitively reflect the 1 O2 levels generated in the tumor tissues by NIR fluorescence and guide optimized PDT conditions in tumor therapy.